URGENSI DAN NILAI KEISLAMAN DALAM KEPEMIMPINAN TRANSFORMASIONAL BERNARD M. BASS DI LEMBAGA PENDIDIKAN BERBASIS KEISLAMAN - Fajar Mustika Violeta; Suwadi (STAI Ma'had Aly Al-Hikam Malang, 2023)
Islamic educational institutions have a central role in producing a generation of Muslims who are faithful, knowledgeable and noble-character. Effective and inspiring leadership is the key to achieve this noble goal. This research aims to explore the urgency of Islamic values in Bernard M. Bass' transformational leadership to improve the quality of Islamic educational institutions. This research is a literature study using qualitative methodology. Data were collected from various sources, including: books, journal articles and websites resources. The results showed that transformational leadership theory can be combined with Islamic values in improving the quality of Islamic education institutions. These values include; The value of trust, hablum minannas, uswatun hasanah, combination of reason (aql) and qalb, and deliberation are analyzed as the moral and ethical foundation of Islamic transformational leadership. Keywords: Islamic Values, Transformational Leadership, Islamic Education Institution